Predictors of Seroconversion of Hepatitis-C Virus in End-Stage Renal Disease Patients - Asma Razzak; Mehwish Qamar; Farzana Adnan; Maria Quershi; Abdul Hameed (ziauddin University, 2024)
Background: Chronic kidney disease (CKD) is a significant health challenge globally. Hemodialysis, the primary treatment for CKD, not only sustains lives but also increases the risk of disease transmission, particularly hepatitis C (HCV), with a 48.9% seroconversion rate. This study aimed to identify factors contributing to HCV seroconversion of hemodialysis patients in Karachi. Methods: A cross-sectional study was conducted at three dialysis units within tertiary care hospitals in Karachi, from June 2022 to June 2023. A total of 141 patients aged between 18 and 65, of any gender, undergoing chronic hemodialysis for a minimum of 6 months, demonstrating good adherence, and possessing comprehensive serological data for HCV (baseline test and follow-up screening) were included. Data was analyzed using SPSS version 27 and a comparison between baseline characteristics and risk factors with seroconversion of HCV was done using independent samples t-test/Chi-square test. A p<0.05 was considered statistically significant. Results: The patients had a mean age of 33.30±8.04 years. Seroconversion occurred in 14.9% of cases, with 21% testing positive for HCV on PCR. Notably, a higher prevalence of blood transfusion history (p=0.002), surgery history (p=0.001), a family history of HCV (p=0.001), dialysis at multiple centers (p=0.001), and initiating dialysis with an arteriovenous fistula (p=0.015) was observed among HCV-positive patients who underwent seroconversion, in comparison to those who remained HCV-negative. Conclusion: A history of blood transfusion and surgery, a family history of HCV, dialysis at multiple centers, and initiation of dialysis with arteriovenous fistula are notable predictors for seroconverted positive HCV patients.